RESILIENCE DAN PSYCHOLOGICAL WELL-BEING KAITANNYA DENGAN SOCIAL INTERACTION ANXIETY PADA MAHASISWA PASCA PANDEMIC COVID-19 - Nur fitriyani Keras; Citra Widyastuti; Arya Fendha Ibnu Shina Arya (Indonesian Journal of Islamic Counseling, 2026)
Indonesia ranks 13th in the world for the highest number of COVID-19 cases. To prevent the spread, the government has implemented social distancing. Almost all places have temporarily closed, including educational institutions. This situation has impacted changes in people's behavior, both in social and educational aspects, particularly the learning process in higher education. This study focuses on a social problem, namely students' awkwardness in interacting, known as social interaction anxiety. In response, individuals can adapt and survive in their social environment, known as resilience. This condition also affects psychological well-being, which is important for self-actualization and development. This study aims to determine the relationship between resilience and psychological well-being simultaneously with social interaction anxiety in students after the COVID-19 pandemic. The method used is a quantitative approach with a psychological scale instrument. The sampling technique used incidental sampling with 505 students as respondents. Data analysis used multiple regression with SPSS 22.0. The results show a significant relationship with a fairly strong correlation.